Locke's moral man - LoLordo, Antonia, 1972- (Oxford : Oxford University Press, 2012)
An original interpretation of John Locke's metaphysics of moral agency, in which to be a moral agent is simply to be free rational, and a person. The author's account bears on Locke's metaphysics and political theory, and helps us understand his wider philosophical project and his accounts of liberty personhood, and rationality.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Locke, John, -- 1632-1704.; Ethics